Pertussis may be the cause of prolonged cough in adolescents and adults in the interepidemic period - Pimentel,Analíria Moraes (2015)
Objective:This study was aimed to evaluate the prevalence of pertussis in adolescents and adults with cough lasting more than 14 days and less than 30 days.Methods:This is a prospective observational study in interepidemic period of pertusis. Ten public health outpatient clinics in the city of Recife, Brazil, were randomly selected for the study. The study population consisted of individuals aged 10 years and over with cough that had lasted between 14 and 30 days. Nasopharyngeal swabs were collected for culture and PCR in order to identify Bordetella pertussis. We adopted the Centers for Disease Control and Prevention in the US (CDC) deﬁnition of cases of pertussis.Results:A total of 192 individuals were identiﬁed as suspected cases. Their mean age was 40.7 years. Pertussis was conﬁrmed in 10 of the 192 suspected cases, with an estimated prevalence of 5.21% (95% conﬁdence interval 2.03-8.38). All cases met the clinical case deﬁnition for pertussis; one suspect had both culture and PCR positive. PCR conﬁrmed 100% of the cases, 7/10 by PCR and 3/10 by epidemiological linkage with a case conﬁrmed by PCR.Conclusion:During an interepidemic period, 1 in 20 cases of prolonged cough had pertussis, suggesting this is an important cause of prolonged cough in adolescents and adults.